Molecular and ionised gas kinematics in a sample of nearby active galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Bianchin, Marina; Riffel, Rogemar A.; Storchi-Bergmann, Thaisa; Riffel, Rogério; Schonell, Astor J.
Abstract: We used Gemini NIFS integral field spectroscopy to analyse the molecular and ionised gas kinematics of six nearby ( z ⩽ 0.015) Seyfert galaxies with a spatial coverage of 0.1 – 0.6 kpc 2 . By fitting the emission-line profiles using multiple Gaussian components we determined that the ionised and hot molecular gas kinematics are dominated by gas outflows and rotation, respectively, even though three objects also present molecular outflows.